THE DYNAMICS OF PERIURBANIZATION AND THE TRANSFORMATION OF PERIURBAN AREAS IN BANDUNG REGENCY - Rahmi Hidayat, Fathiyah
The phenomenon of urban expansion continues around the world because of the development process that occurs in big cities. Through this development process, the city as a living entity continues to grow beyond administrative boundaries, creating new activity centers outside the built-up area of the city. This new activity center can change the area which was originally a rural area into an area mixed with urban activities and characteristics to create a new delineation, called the peri urban area. This area has a distinctive characteristic, namely a mixture of rural and urban characteristics or referred to as a gray area located between urban and rural areas. Until now, there is no specific criteria that can be used as indicator in determining the delineation of peri urban areas. Peri urbanization in Indonesia is not a new phenomenon, this transformation process initially occurred around the capital city of Jakarta. Connectivity to support Jakarta's urban activities has a direct impact on the city of Bandung to form a new urban agglomeration, called Metropolitan Bandung Raya (MBR). Bandung as one of the metropolitan areas in Indonesia continues to show changes in the structure of the city and the intensification of the phenomenon of peri urbanization to Bandung Regency. The more developed Bandung Regency, it is necessary to conduct a study that can describe this peri urbanization phenomenon contextually. Therefore, this study was conducted to be able to see the dynamics of the transformation of the region within the framework of peri-urbanization. This research is expected to be able to provide an empirical explanation and contribute to the global discourse surrounding related to the theoretical peri-urbanization process. To identify peri urbanization in Bandung Regency, the typology of spatial configuration, components, indicators, and variables that can be applied is formulated in accordance with the theoretical basis regarding peri urban. These variables are then derived into a list of data requirements that can represent the components and indicators that have been determined previously. Then theiv clustering analysis process was carried out using the K-Means clustering analysis method using SPSS as analysis tools. The output of this analysis is a spatial typology in which there is a peri urban area. It will be used as an input for further analysis to see the dynamics of peri urbanization in Bandung Regency based on spatial, social, and economic components. The output of cluster analysis is the delineation of the peri urban are which was divided into urban fringe and urban periphery. There were 20 sub-districts identified as peri urban areas, ten sub-districts each. The condition of each of these areas becomes a further analytical framework to identify spatial, social, and economic transformations. Thus, it was concluded that during the 2000 to 2020 observation year, Bandung Regency has been experiencing a regional transformation in which there were areas identified as peri urban areas.